Multiplexed, Real-Time PCR for Quantitative Detection of Human Adenovirus - Gu, Z. (American Society for Microbiology, 2003)
Adenovirus infection is becoming increasingly recognized as a cause of morbidity and mortality in the immunosuppressed patient population. While early detection and quantitation of adenovirus in peripheral blood has been suggested as a means of directing and monitoring antiviral therapy in these patients, few methods have been published, particularly with respect to viral quantitation. A multiplexed real-time PCR assay was developed that can quantitatively detect a wide range of known serotypes of human adenovirus, including all of subgroups A to C. This assay was compared to a qualitative, Southern blot-based PCR assay by using 45 peripheral blood specimens from 16 patients. There was 100% concordance between the two tests in terms of qualitative results. The real-time assay detected adenovirus in patient samples at levels from <200 to 266,681 copies/ml of blood. By using control viral samples, sensitivity was demonstrated to less than 10 copies of viral genome per reaction and quantitative linearity was demonstrated from 10 to 10(6) copies of input viral DNA. Equivalent sensitivity and linearity were demonstrated for 15 different reference serotypes of adenovirus. Eleven other viral serotypes have complete target region sequence homology to one or more of the strains tested. No cross-reactivity was noted with other commonly isolated viral species. Sequence analysis showed no significant homology with any other human pathogens (bacterial or viral). This assay allows rapid, sensitive, and specific quantitation of adenovirus and may have a significant impact on the care of immunocompromised patients at risk for disseminated viral infection.